EDUKASI TIPE KEPRIBADIAN DALAM PENCEGAHAN FENOMENA CELEBRITY WORSHIP SYNDROME (CWS) DAN FEAR OF MISSING OUT (FOMO) DI KALANGAN REMAJA - Puji Setya Rini, Puji Setya Rini; Aizah, Rosmitha (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
Teenagers who lack sufficient knowledge often face challenges due to problems. Teenagers are unprepared for the physical and psychological changes that will occur, which can be traumatic for them. Therefore, understanding sexuality is crucial. This knowledge must be obtained accurately and comprehensively so that they are not afraid to face the responsibilities that must be fulfilled at this stage of their development. The negative impacts of CWS and FoMO make someone unable to enjoy togetherness in the real world to the fullest, indifferent to their surroundings, disturbed sleep, eating disorders, and feelings of inadequacy with what they already have. The implementation of community service activities was carried out using a lecture method, distributed pre-post-test questionnaires for health education. The data obtained were univariate data only describing an increase in knowledge. The results of the community service activities obtained were mostly FOMO in the moderate category (31 respondents (62%) and CWS in the high category (24 respondents (48%). After the community service activities were carried out, it is hoped that adolescents will be monitored, especially regarding FOMO and CWS.